2012
DOI: 10.3168/jds.2010-3458
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield affects time budget of dairy cows in tie-stalls

Abstract: Effective selection in breeding programs and improved management has increased the milk production per cow. However, the effects of the increased yield on behavior have not yet been clarified. We investigated the effect of milk yield on the time budget of 29 Finnish Ayrshire cows in the same stage of lactation kept in tie-stalls. The time spent lying, eating, ruminating, lying inactive without ruminating, and lying with the neck muscles relaxed, as well as the milk yield of primiparous and multiparous cows wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
49
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 39 publications
10
49
4
Order By: Relevance
“…The median lying time of 12.5 h is similar to the 13 h suggested as the amount of time lying down that cows are motivated to work for . Some of the very large variation between cows was related to parity and stage of lactation agreeing with previous research (Norring et al, 2012;Vasseur et al, 2012). The daily duration of time spent lying down increased as DIM increased, mainly due to an increase in mean bout duration, while older cows had a reduced frequency of lying bouts than younger ones.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The median lying time of 12.5 h is similar to the 13 h suggested as the amount of time lying down that cows are motivated to work for . Some of the very large variation between cows was related to parity and stage of lactation agreeing with previous research (Norring et al, 2012;Vasseur et al, 2012). The daily duration of time spent lying down increased as DIM increased, mainly due to an increase in mean bout duration, while older cows had a reduced frequency of lying bouts than younger ones.…”
Section: Discussionsupporting
confidence: 83%
“…Some of the variation between farms is due to milk yield, with cows on the higher producing farms lying down for longer than cows on lower producing farms. This is the opposite from the results of Norring et al (2012) who reported that high producing cows in tie-stall farms lay down for less time than low producing cows. Possible explanations for this contradictory finding could be sample size, cattle breed or stage of lactation as the findings from Norring et al (2012) were based on a study of 29 Finnish Ayrshire cows in their 8th week of lactation.…”
Section: Daily Durationcontrasting
confidence: 83%
See 2 more Smart Citations
“…In the present study, 3 large peaks in rumination activity were observed throughout the day, coinciding with the periods of lowest feeding activity. Norring et al (2012) observed that …”
Section: Discussionmentioning
confidence: 97%